2016
DOI: 10.1094/phyto-02-16-0091-r
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aPi9-Containing Rice Germplasm with a Newly Developed Robust Marker

Abstract: The Pi9 gene in rice, originating from Oryza minuta, is an effective resistance gene for controlling rice blast disease. However, currently available linked DNA markers do not accurately identify the function of Pi9, thus hindering its efficient incorporation into new cultivars through marker-assisted selection (MAS). In addition, no known Pi9-containing rice germplasm is available to breeders. In the present study, DNA sequence variation of Pi9 alleles and their family members was analyzed in 40 diverse rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Recently, Tian et al. () reported the development of an InDel marker and a CAPS marker for genotyping of Pi2 and Pi9 targeting the Pi2/Pi9 locus; Scheuermann and Jia () also developed a dominant marker to identify Pi9 ‐containing rice germplasm. In the study, we report on the development of a gene‐targeted and codominant marker for discriminating the Pi2 and Pi9 genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Tian et al. () reported the development of an InDel marker and a CAPS marker for genotyping of Pi2 and Pi9 targeting the Pi2/Pi9 locus; Scheuermann and Jia () also developed a dominant marker to identify Pi9 ‐containing rice germplasm. In the study, we report on the development of a gene‐targeted and codominant marker for discriminating the Pi2 and Pi9 genes.…”
Section: Discussionmentioning
confidence: 99%
“…The Pi2 and Pi9 in rice were two well-known R genes showing very broad-spectrum resistance to most of M. oryzae isolates collected from 13 countries (Liu et al 2002). Recently, Tian et al (2016) reported the development of an InDel marker and a CAPS marker for genotyping of Pi2 and Pi9 targeting the Pi2/Pi9 locus; Scheuermann and Jia (2016) also developed a dominant marker to identify Pi9-containing rice germplasm. In the study, we report on the development of a gene-targeted and codominant marker for discriminating the Pi2 and Pi9 genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic markers linked or derived from the cloned R genes were developed to predict resistance function and to monitor the existence of each of the R genes [31][32][33][44][45][46][47][48][49][50][51][52]. Differential blast races were identified ( Table 2) and have been used to validate their predicted resistance efficacies.…”
Section: Effective Major R Genesmentioning
confidence: 99%